Abonelik temelli isteğe bağlı video hizmetlerine (s-vod)yönelik tüketici ağızdan ağıza iletişim ve üyelik yenilemedavranışının incelenmesi-netflix örneği - GÜSAN KÖSE, GÖZDE; KELEMCİ, GÜLPINAR (My University, 2022)
Teknolojinin gelişimi ve esas olarak internetin evrimi, günümüz iş yapma şeklini değiştirmiş ve geliştirmiştir. Bu durum işletmeleri, müşterilerin gereksinimlerini karşılamak için değişime uyum sağlamak zorunda bırakmış ve yeni medya olarak adlandırılan dijital platformlar ortaya çıkmıştır. Bu bağlamda, şu anda S-VoD hizmetinde dünyada lider ve Türkiye’de de faaliyet gösteren dijital platform Netflix özelindeki bu çalışmanın amacı, ağızdan ağıza iletişim ve üyelik yenileme davranışları ile içerik kalitesi, kişiselleştirme, gezinme-görsel tasarım ve fiyat adaleti algısı değişkenleri arasındaki ilişkisinin incelenmesi ve bu ilişkiler temelinde teorik çerçevede bir model geliştirmek hedeflenmiştir. Ayrıca, bu ilişkilerin gelişmeleri kaçırma korkusu düzeyine (yüksek ve düşük) göre farklılaşıp farklılaşmadığının incelenmesi de çalışmanın bir diğer amacını oluşturmaktadır.

The evolution of technology, and mainly the evolution of the Internet, has improved the way business is done. Nowadays, most services are offered through a website or through an app, as it is much more convenient and suitable for the customer and digital platforms, which are called new media, have emerged. In this context, Netflix, the first digital platform operating in Turkey, constitutes the scope of the research. The first aim of this study is to examine the relationsship between the content quality, personalization, navigation-visual design and price fairness perception variables, as well as word-of-mouth communication and subscription renewal behaviors. Another aim of the study is to develop a model in the theoretical framework on the basis of these relations. The thirth aim of this study is to examine the relationship between word-of-mouth communication and subscription renewal behavior and the variables of content quality, personalization, navigation and visual design, and price justice perception. Besides another aim of the study is to examine whether word of mouth communication and subscription renewal behavior differ according to the level of fear of missing out (high and low
Examination of consumer word of mouth and subscription renewal behavior for subscription-based video-on-demand services (s-vod) in the case of netflix
Keywords: S-VoD Services; Subscription Renewal Behavior; Wom; Fomo - fear of missing out; S-VoD Hizmetleri; Üyelik Yenileme Davranışı; Ağızdan Ağıza İletişim; Gelişmeleri Kaçırma Korkusu